2016
DOI: 10.1016/j.bbi.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil depletion after subarachnoid hemorrhage improves memory via NMDA receptors

Abstract: Cognitive deficits after aneurysmal subarachnoid hemorrhage (SAH) are common and disabling. Patients who experience delayed deterioration associated with vasospasm are likely to have cognitive deficits, particularly problems with executive function, verbal and spatial memory. Here, we report neurophysiological and pathological mechanisms underlying behavioral deficits in a murine model of SAH. On tests of spatial memory, animals with SAH performed worse than sham animals in the first week and one month after S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 54 publications
(80 reference statements)
1
68
0
Order By: Relevance
“…The third day after the initial hemorrhage is suggested to host the initial peak of inflammation in human and animal studies. Cerebral spinal fluid neutrophilia on the third day in patients with SAH was an independent predictor of the later development of DCI in a previous study 39 , and depletion of neutrophils three days after SAH in a murine model mitigated tissue inflammation, reversed cerebral vasoconstriction and restored memory mechanisms at day 6 40 . Finally, none of the patients from our cohort developed infections during the seven-day period of observation, minimizing the possibility of observing leukocytosis secondary to bacterial infections.…”
Section: Discussionmentioning
confidence: 64%
“…The third day after the initial hemorrhage is suggested to host the initial peak of inflammation in human and animal studies. Cerebral spinal fluid neutrophilia on the third day in patients with SAH was an independent predictor of the later development of DCI in a previous study 39 , and depletion of neutrophils three days after SAH in a murine model mitigated tissue inflammation, reversed cerebral vasoconstriction and restored memory mechanisms at day 6 40 . Finally, none of the patients from our cohort developed infections during the seven-day period of observation, minimizing the possibility of observing leukocytosis secondary to bacterial infections.…”
Section: Discussionmentioning
confidence: 64%
“…In our model of sterile brain injury, peripheral depletion of neutrophils impedes the development of spatial memory deficits after SAH 4 . To determine whether neutrophil effector function plays a role in these deficits, mice deficient in the neutrophil effector proteins myeloperoxidase, elastase and NADPH oxidase (that have been previously implicated in neuronal damage after ischemic stroke) 8,10,17 , were tested ( Fig.…”
Section: The Neutrophil Enzyme Myeloperoxidase Is Critical To the Devmentioning
confidence: 80%
“…Previous findings from our laboratory demonstrate that SAH leads to delayed cognitive deficits in mice 5 . These deficits are attributed to the loss of long-term potentiation (LTP) in the hippocampus 4 In addition, the mechanism(s) through which MPO's activity affects neurons is not clear.…”
Section: Myeloperoxidase Directly Modulates Neuronal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Herz et al [11] have recently demonstrated that CXCR2 antagonization reduced neurological deficits and infarct volumes following middle cerebral artery occlusion and this was associated with reduced neutrophil infiltration into the CNS. Similarly, depletion of neutrophils following subarachnoid hemorrhage was found to improve memory in a model of aneurysmal subarachnoid hemorrhage (SAH) [33]. Additionally, Zenaro et al [49] have demonstrated a role for the adhesion molecule lymphocyte function-associated antigen 1 (LFA-1) in promoting neutrophil accumulation within the CNS and amplifying AD-like pathology in transgenic models of Alzheimer's disease (AD).…”
Section: Neutrophils and Viral-induced Demyelinationmentioning
confidence: 99%